Business analyst (Henry Stewart Talks, 2026)
Role and responsibilities of a Business Analyst, Skills and competencies for Business Analysts, Methodologies used by Business Analysts, Process optimisation and decision support, Challenges faced by Business Analysts, Importance of communication and actionable insights, Future demand and career prospects for Business Analysts